2015
DOI: 10.4102/sajems.v18i4.1239
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic and complementary effects of supply chain justice and integration practices on supply chain performance: A conceptual framework and research propositions

Abstract: In recent years, firms have been using their supply chain integration (SCI) as a competitive weapon in the intensive, globalised competitive arena. The contingent perspective in supply chain management maintains that it is necessary to observe the interaction between SCI practices and supply chain justice. A critical issue to be resolved is whether this fit leads to synergistic and complementary effects on supply chain performance. In order to contribute to this research problem, we analysed supply chain justi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…Their study concluded that dependence inhibits SCI by encouraging opportunistic tendencies, while interdependence enhanced SCI by promoting the pursuit of overlapping SCM objectives. Ziaullah et al (2015) investigated the interaction effects of SCI and SC justice on SC performance within the South African context. Recently, some scholars examined the influence of three drivers of SC performance, namely, inter-firm trust, commitment and relationship durability, within the South African food retail industry (Ngouapegne and Chinomona, 2019).…”
Section: African Perspective Of Scmmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study concluded that dependence inhibits SCI by encouraging opportunistic tendencies, while interdependence enhanced SCI by promoting the pursuit of overlapping SCM objectives. Ziaullah et al (2015) investigated the interaction effects of SCI and SC justice on SC performance within the South African context. Recently, some scholars examined the influence of three drivers of SC performance, namely, inter-firm trust, commitment and relationship durability, within the South African food retail industry (Ngouapegne and Chinomona, 2019).…”
Section: African Perspective Of Scmmentioning
confidence: 99%
“…Ziaullah et al (2015) investigated the interaction effects of SCI and SC justice on SC performance within the South African context. Recently, some scholars examined the influence of three drivers of SC performance, namely, inter-firm trust, commitment and relationship durability, within the South African food retail industry (Ngouapegne and Chinomona, 2019).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Constraints on SC in developing and established nations are likely to differ, emphasizing the need for more similar research in emerging countries (Lee et al, 2016). While empirical research into SC integration, SC capabilities, and operational performance is still lacking in Pakistan, the recent appearance of such studies is encouraging (Ziaullah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%